REKOMENDASI STAND DAN PENGEMBANGAN SISTEM PEMESANAN MENGGUNAKAN METODE SCRUM DAN ANALISIS EFEKTIVITASNYA TERHADAP MASYARAKAT: STUDI KASUS DI KOTA BATAM - Evan Charles; Herma (JURNAL ILMIAH BETRIK, 2023)
Nowadays, college students don’t have much time to spend in the university canteen and waiting for food in long queues. Sometimes they will not get food because of insufficient rest time. The study aims to develop a web-based ordering system that focuses on mobile and includes a recommendation system. This project helps students to find out information on menu availability and place orders for food menus earlier without having to stand in long queues. The website was built using frameworks such as Nuxt and Laravel along with Agile Scrum method. The website was then used to analyze the effectiveness usage of the ordering system using Technology Acceptance Model (TAM). Hypothesis testing was carried out through linear regression using SmartPLS software. The results of this study expected to be useful and improve the services, avoid long queues and also save time in placing orders without being affected by rest hours.